Понятійні ознаки концепту CHARM / ЧАРІВНІСТЬ в англійській та українській мовах - Томчаковська, Юлія Олегівна; Томчаковська, Ю. О.; Томчаковская, Юлия Олеговна; Tomchakovska, Yuliia О. (My University, 2017)
Стаття присвячена контрастивному дослідженню лінгвокультурного концепту CHARM / ЧАРІВНІСТЬ в англійській та українській мовах. В роботі розглядаються понятійні ознаки цих концептів на основі компонентного аналізу словникових дефініцій лексем-номінантів.

linguocultural concept CHARM / ЧАРІВНІСТЬ in the English and Ukrainian languages. The work considers notional features of the given concepts on the basis of componential analysis of the lexemes-nominations. In modern linguistics “concept” is defined as a mental unity which consists of heterogeneous units. The complex structure of any concept includes different features, such as motivational, notional, associative and evaluative. Notional features are foregrounded in the dictionary definitions of the lexemes-nominations as a system of semantic components (semes) and in the synonymic nominations. The lexemes charm and чарівність are direct nominations of the corresponding concepts in the English and Ukrainian languages. The study of their etymology, dictionary definitions and lexical valency is the most informative way of revealing the structure of the analyzed concepts.
Томчаковська Ю. О. Понятійні ознаки концепту CHARM / ЧАРІВНІСТЬ в англійській та українській мовах / Ю. О. Томчаковська // Записки з романо-германської філології. – Вип. 1 (38) – 2017. – С. 122-129.
Keywords: концепт; понятійна ознака; компонентний аналіз; чарівність; concept; notional feature; componential analysis; charm